Pregnancy and care practices (2010)
The purposeofthisresearch istovalue thecarepractices that mothers perform on themselves and on the baby to whom she is going to give birth. 150 pregnant women that go to the Centro Operativo Local Engativá medical facility, registered on project 7317: "Preganant Families: healthy and desired babies of the Administrative DepartmentofSocialWellbeing", using a quantitative and descriptive methodology. We applied the "Instrument to value those care practices that are performed on themselves and on the baby to whom they are going to give birth during the prenatal stage", It was carried out by research nurses of the Nursing Faculty at the Universidad Nacional de Colombia (1), and the data were analized in a descriptive manner by frequency and percentages. The results were obtained via a six dimension analysis that constitute the instrument where one identifies and characterizes the care practice. We conclude that in the pregnant group there is a regular care practice in the dimensions of : prenatal estimulation (56,67%), exercise and rest (78%), feeding paterns (82,67%) and good care practice in terms of hygine and personal care (88%), support systems (82%) and none beneficial substances (78,67%).